The use of GNSS receivers in smartphones as high precision positioners - Fabricio, Rodolfo Nogueira Leal; do Nascimento, G. A. Gomes (The International Hydrographic Review, 2025)
In recent decades, there has been a growing increase in the use of GNSS geotechnology and the creation of new frequencies, such as L5, which help with positioning accuracy. These advances made possible the use of mobile devices for positioning activities. Given the above, this work aimed to analyze the possibility of using smartphones as high-precision* positioners, through the comparison of data collected by high-precision receivers and cell phones, and post-processed data. Finally, it was concluded that although technology has favored the work of positioning by cell phone, it still cannot be used in jobs that require greater precision, for example in hydrographic surveys.